Finite Element Studies of Skid Resistance under Hot Weather Condition. Issue 40 (December 2018) - Tang, Tianchi; Anupam, Kumar; Kasbergen, Cor; Kogbara, Reginald; Scarpas, Athanasios; Masad, Eyad
The skid resistance of a pavement surface is an important characteristic that influences traffic safety. Previous studies have shown that skid resistance varies with temperature. However, relatively limited work has been carried out to study the effect of temperature on skid resistance in hot climates. Recent developments in computing and computational methods have encouraged researchers to analyze the mechanics of the tire-pavement interaction phenomenon. The aim of this paper is to develop a thermo-mechanical tire pavement interaction model that would allow more robust and realistic modeling of skid resistance using the Finite Element (FE) method. The results of this model were validated using field tests that were performed in the State of Qatar. Consequently, the validated FE model was used to quantify the effect of factors such as speed, inflation pressure, wheel load, and ambient temperature on the skid resistance/braking distance. The developed model and analysis methods are expected to be valuable for road engineers to evaluate the skid resistance and braking distance for pavement management and performance prediction purposes.